High Sensitivity Humidity Sensors Based on Zn1−xSnxO Nanostructures and Plausible Sensing Mechanism. Issue 16 (12th June 2022) - Wang, Qiuhui; Zhang, Xuguo; Xu, Jie; Chen, Zixin; Kuang, Xuliang; Zeng, Jundong; Liu, Weijing; Bai, Wei; Tang, Xiaodong
Abstract : Four kinds of Zn1− x Sn x O (X = 0%, 1%, 3%, 5%) nanowires with different concentrations are synthesized by a hydrothermal method. The samples are characterized and measured by X‐ray diffraction (XRD), scanning electron microscopy (SEM), and X‐Ray photoelectron spectroscopy (XPS). Then, the nanostructures are arranged on predesigned Ti/Au electrodes through the dielectrophoresis (DEP) nanomanipulation technique to fabricate four humidity sensors and investigate the humidity sensing properties. The results demonstrate that the Sn doping process can regulate the surface oxygen vacancy concentration and improve the performance of humidity sensors. In particular, the 3% Sn‐doped ZnO humidity sensor exhibits higher sensitivity with a response/recovery time of 4s/2s, lower hysteresis, and better repeatability. In addition, the sensing mechanisms are discussed in depth by combining complex impedance spectroscopy and multilayer adsorption theory. The obtained results indicate that a certain amount of Sn doping can introduce oxygen vacancies, adjust the lattice and surface state, and hence modulate the sensing properties of ZnO nanosensors. Abstract : Sn ions are successfully doped into ZnO lattice and regulate the materials oxygen defect concentration, making humidity sensors on the predesigned Ti/Au interdigital electrode by a dielectrophoresis method. The humidity sensing performance of ZnO is significantly enhanced after Sn doping. The humidity sensing mechanism of the sensors is studied by combining complex impedance spectroscopy and Freundlich isotherm modelling.